Polithematical rubricators of VINITI. General characteristics - Прокопчик, Мария (Knygotyra, 1983)
In the article an attempt is made to check the general characteristics of the system of rubricators worked out in VINITI during the last two decades. It deals with the main features of every rubricator, shows their logical structure, codes, systems of subject headings, criterions of their choice. The experience of elaborating the rubricators makes basis to the Rubricator of the State automatized system of scientific and technical information. This Rubricator will be the main classification language in the complex of the linguistical guaranteeing of the system. The comission of the Rubricator will make it possible to unificate the structure and functions of the rubricators for various informational institutions. This enables to organize the exchange of information between various informational institutions on machine and tradicional carriers and to raise the effectivity of the information service.